Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Keterampilan Berpikir Kritis Siswa - Marissa Faradilla; Darsikin; Marungkil Pasaribu (Jurnal Kreatif Online, 2021)
This study aims to determine the effect of the guided inquiry learning model on students' critical thinking skills on work and energy. The research method used was quasi-experimental designs with research designs, pretest-posttest control group designs. The research sample was class VIIB as the experimental class (n=30) and class VIIC as the control class (n=30) which was selected by purposive sampling technique. The research instrument used was a test of critical thinking skills in the form of essay questions. Data analysis was performed using non-parametric statistics and two-party t-test at a significance level of 0.05. The results of the analysis show that tcount>ttable=2,15>1,67, so H_0 is rejected and H1 is accepted. This shows that there are differences in critical thinking skills between students who use the Guided Inquiry learning model and groups of students who use conventional learning models (direct interaction). It can be concluded that there is an influence of the guided inquiry learning model on the critical thinking skills of seventh grade students of SMP Negeri 9 Palu.